2007
DOI: 10.1254/jphs.fp0061173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some H1-Antagonists on the Sleep-Wake Cycle in Sleep-Disturbed Rats

Abstract: Abstract. The present study was undertaken to investigate the effects of some H 1 -antagonists on the sleep-wake cycle in sleep-disturbed rats in comparison with those of nitrazepam. Electrodes were chronically implanted into the frontal cortex and the dorsal neck muscle of rats for the electroencephalogram (EEG) and electromyogram (EMG), respectively. EEG and EMG were recorded with an electroencephalograph. SleepSign ver. 2.0 was used for EEG and EMG analysis. The total times of waking, non-rapid eye movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…From these findings, it is reasonable to conclude that donepezil caused sleep disturbance in animals. On the other hand, in a clinical study, Ancoli-Israel et al (8) showed that donepezil tended to worsen the Pittsburgh Sleep Quality Index (PSQI), used as an indicator of sleep quantity and quality; therefore, we studied the effect on delta activity during non-REM sleep to investigate sleep quality in rats (15,21). As shown in Table 2, donepezil caused a significant decrease in delta activity at 1 -2 h. As shown in Figs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…From these findings, it is reasonable to conclude that donepezil caused sleep disturbance in animals. On the other hand, in a clinical study, Ancoli-Israel et al (8) showed that donepezil tended to worsen the Pittsburgh Sleep Quality Index (PSQI), used as an indicator of sleep quantity and quality; therefore, we studied the effect on delta activity during non-REM sleep to investigate sleep quality in rats (15,21). As shown in Table 2, donepezil caused a significant decrease in delta activity at 1 -2 h. As shown in Figs.…”
Section: Discussionmentioning
confidence: 95%
“…2.0. The power spectrum densities, integrated and averaged, could be divided into 4 frequency areas: delta wave (0.5 -4 Hz), theta wave (4 -8 Hz), alpha wave (8 -13 Hz), and beta wave (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Delta activity (%) was calculated by the following equation: Delta activity (%) = delta wave power density in the drug administration period / delta wave power density in the vehicle administration period in each animal × 100.…”
Section: Calculation Of Delta Activity During Non-rem Sleepmentioning
confidence: 99%
“…Tokunaga et al (24) also reported that diphenhydramine only had a sleep-inducing effect on sleep-disturbed rats. Furthermore, it has been reported that diphenhydramine shortened the sleep latency in humans (25).…”
Section: Discussionmentioning
confidence: 96%
“…2.0, according to the criteria previously described (13,14). As a final step, the defined sleepwake stages were examined visually, and corrected if…”
Section: Sleep-wake State Analysismentioning
confidence: 99%